Isolation and characterization of thermo-proteolytic bacteria from hot springs in the Mariarotu Tourism Area (MTA), Yapen Islands, Papua - Dirk Y.P. Runtuboi; Yulindra M. Numberi; Fawuni G.A.G. Rumbrawer (Jurnal Biologi Papua, 2026)
Thermophilic bacteria are able to survive in extreme environmental conditions with high temperatures, generally ranging from 45–80°C. Thermophilic bacteria are also capable of producing protease enzymes. This study aimed to isolate and identify thermophilic bacteria from the Mariarotu hot spring, Yapen Islands Regency, Papua. The method used in this study was a survey followed by laboratory identification. Water samples were collected from two hot spring points with temperatures of 39–49°C. A total of six isolates were obtained and characterized based on macroscopic, microscopic, and biochemical tests. Based on this characterization, all isolates belonged to the genus Bacillus. These results indicate that the Mariarotu hot spring has potential as a habitat for thermophilic bacteria producing thermostable enzymes with possible applications in biotechnology. Further molecular-based studies are required for more accurate species identification.